„Tak, nie zna mnie nikt!”. Dziennik intymny Marceliny Kulikowskiej - Warchoł, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article attempts to return Marcelina Kulikowska to the historical and literary discourse and reconstruct her biography and worldview on the basis of diaries that she wrote from 1894 until her suicide in 1910. In the analysis, the author provides information from the original entries in the diary. She also reveals in a critical way the current interpretation of the diary, proposing another view instead that changes the superficial opinion that has grown around the poet’s work.